Freeze drying technology and its impact on the characteristics of kopyor coconut flesh - Faleh Setia Budi; Alyssa Nesiananda; Azis Boing Sitanggang (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2024)
Kopyor coconut is one of Indonesia's origin germplasms that has a high economic value. Theflesh of the kopyor coconuts is quickly damaged characterized by rancidity due to the presence of microorganisms. This study aimed to investigate the effect of blanching and freeze-drying processes, considering the factors of drying duration and pressure, on the quality of kopyor coconut Flesh. The kopyor coconuts used in this studywere obtained from Ciomas Plantation IOPRI Bogor Unit, Bogor, West Java. The kopyor coconut flesh was grouped into two categories: one treated with steam blanching at 100 °C for 10 min and the other without blanching treatment. Freeze-drying processes were carried out for 12, 24, 48, and 72 h and at absolute pressures of 0.01 and 0.05 mbar. The characteristics observed were the moisture content, pH, whiteness index,and free fatty acids content (FFA).The combining of steam blanching and freeze-drying process for 48 h and a pressure of 0.01 mbar was the best treatment. The dried product had uniform texture with moisture content of 5.31%, whiteness index of 89.67%, pH of 7,04 and free fatty acid of 0,51%. These values indicated that the quality of dried fruit complied with the Indonesian standard of dried fruit quality (SNI 3710:2018).